Paradigma Ibadah Haji dan Umroh Ditinjau Berdasarkan Perspektif Hukum Islam dan Hukum Positif di Indonesia - Wulandari, Suci; Azizi, Salman Daffa Nur; Hidayat, Rifqi Thariq (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2023)
Indonesia is a country where the majority of its citizens embrace Islam. So Indonesia has become part of the largest Muslim countries in the world. As a Muslim, it is appropriate to carry out the Shari'a and religious rules correctly, such as carrying out the pillars of Islam. One of the pillars of Islam is the fifth pillar of Islam, namely the Hajj pilgrimage for anyone who is able. The word capable means being physically, mentally, and financially capable. The Hajj and Umrah pilgrimages are recommendations that should be carried out if someone has been declared baligh or mukhallaf. In its implementation, it turns out that Indonesia has provided regulations that are expected to provide a legal umbrella other than Islamic law. This paper uses a normative approach and data taken from various relevant literature sources based on the literature study. This article aims to determine the legal basis for implementing the Hajj and Umrah pilgrimages from the perspective of Islamic law and positive law in Indonesia.